A case report of robotic-guided prone transpsoas lumbar fusion in a patient with lumbar pseudarthrosis, adjacent segment disease, and degenerative scoliosis. (May 2022) - Shahrestani, Shane; Brown, Nolan J.; Acharya, Nischal; Diaz-Aguilar, Luis Daniel; Pham, Martin H.; Taylor, William R.
Abstract: Background: Surgical treatment of scoliosis includes long and invasive multi-level instrumentation and correction which may result in high rates of postoperative complications, especially in elderly patients with osteopenia or multiple comorbidities. Minimally invasive surgical options may benefit these patients. Case description: A 73-year-old female patient with a history of degenerative lumbar scoliosis, L4–5 pseudarthrosis, and resulting L5-S1 adjacent segment following prior unsuccessful lateral L4–5 interbody fusion presented to the clinic with severe lower back pain and lower extremity radiculopathy. The decision was made to proceed with surgical correction via a robotic-guided prone transpsoas (PTP) approach, which is a novel approach similar to lateral lumbar interbody fusion (LLIF) with the patient in a prone decubitus position. Excellent spinal alignment was achieved with no complications. On two-month follow-up, imaging revealed pedicle screws at the L3, L4, L5 levels and at the sacrum without change and continued interbody cages position with no signs or symptoms of infection. Discussion: Minimally invasive procedures have demonstrated benefit in spine surgery especially for at risk populations. The LLIF procedure has been well established for use in a wide range of spinal pathologies given its noted benefits in increasing spinal column stability through posterior fixation and indirect decompression. However, only marginal improvements in segmental lordosis are expected and there are reports of neurological complications. The PTP procedure has emerged as an alternative to LLIF for the treatment of spinopelvic pathologies. This approach enables greater improvements to spinal lordosis through single-position surgery while simultaneously reducing intraoperative repositioning and providing the known benefits of lateral interbody surgery. Conclusion: Our experience suggests that the PTP approach is safe and effective because it does not require patient repositioning, easily interfaces with robotic guidance, and achieves increased lordosis gains via the prone positional effect compared to LLIF and comparable approaches. Highlights: Prone Transpoas (PTP) approach allows for excellent spinal alignment Prone decubitus position of PTP increases spinopelvic alignment compared to lateral lumbar interbody fusion PTP has been shown to enable treatment of lumbar pathologies in a single-position surgery with reduced flip time Complex cases can be managed using the PTP approach to improve lordosis The PTP approach provides an ideal position for intraoperative robotic guidance to enhance surgeon skill